ANALISIS FAKTOR INTERNAL YANG MEMPENGARUHI KREDIT MACET PADA KOPERASI SIMPAN PINJAM - Elsa Regita Cahyani; Sutrisno Sutrisno; Idang Nurodin (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2020)
The purpose of this study toGetahui The influence of internal factors on the bad credit cooperatives keep borrowing simultaneously and significantly. The variables used in This study were internal factors, and credit was jammed. The method used in this study is quantitative with associative type. Data collection techniques are primary by spreading questionnaires to respondents while secondary data by collecting corporate documents and literature studies. The population and samples taken in this study as much as 50 respondents included cooperative managers and borrowers jammed by the main cooperative Citra Cibadak Kab. Sukabumi. Data analysis techniques using validity, reliability, normality, multiple linear regression and partial T-tests.The results of the study using SPSS 26 for Windows can be concluded that the internal factor has a positive and significant effect on the bad credit with its significance value of 0.001 > 0.05 and the test result that the Tcount > Ttable is 3.665 > 1.677 Hence the Ha hypothesis accepted and Ho rejected. Keywords: internal factor, bad credit